Experiences of patients with age-related macular degeneration receiving anti-vascular endothelial growth factor therapy: A qualitative study. (September 2013) - Burton, Amy E; Shaw, Rachel; Gibson, Jonathan
The societal cost for the average health authority in the United Kingdom for the care of wet age-related macular degeneration (AMD) has been suggested to be around £7.4 million. It is vital that the best possible care based on the best available evidence is provided to reduce the impact of AMD on patients' lives and the financial cost to the health-care system. This study explored the experiences of AMD patients treated with intravitreal ranibizumab injections. Three semi-structured interviews were conducted with seven participants over the course of 18 months. Transcripts were analysed using interpretative phenomenological analysis. Analysis identified four themes: preparing for treatment, the treatment process, patient–provider communication, and results of treatment. Patient experiences highlighted the need to move away from the reliance on letters for information provision, and the need for clearer guidelines about when to cease AMD treatment. Interviews highlighted the need for the inclusion of rigorous qualitative evidence with experiential data in future good clinical practice guideline development for AMD.